Tetrazole-based deoxyamodiaquines: Synthesis, ADME/PK profiling and pharmacological evaluation as potential antimalarial agents - Tukulula, Matshawandile; Njoroge, Mathew; Mugumbate, Grace C.; Gut, Jiri; Rosenthal, Philip J.; Barteau, Samuel; Streckfuss, Judith; Heudi, Olivier; Kameni-Tcheudji, Jacques; Chibale, Kelly (Elsevier, 2022)
A series of new deoxyamodiaquine-based compounds was synthesized via the modified TMSN3-Ugi multi-component reaction and evaluated in vitro for antiplasmodial activity. The most potent compounds, 6b, 6c and 6j, showed IC50 values in the range of 6–77 nM against chloroquine-resistant K1- and W2-strains of Plasmodium falciparum. In vitro ADME characterization of frontrunner compounds 6b and 6c indicates that these two compounds are rapidly metabolized and have a high clearance rate in human and rat liver microsomes. This result correlated well with an in vivo pharmacokinetics study, which showed low bioavailability of 6c in rats. Tentative metabolite identification was determined by LC–MS and suggested metabolic lability of groups attached to the tertiary nitrogen. Preliminary studies on 6b and 6c suggested strong inhibitory activity against the major CYP450 enzymes. In silico docking studies were used to rationalize strong inhibition of CYP3A4 by 6c. Full characterization and biological evaluation of the metabolites is currently underway in our laboratories.